The impact of leadership and organizational context on the acceptability of unethical HRM practices - Simões, E. (2020)
Recent research has found that human resource (HR) practitioners judge the acceptability of ethically questionable practices based on the importance their organization attributes to specific features: ethical infrastructure (e.g., codes of conduct) and corporate social responsibility (CSR) practices. The present study sought to evaluate the effects of ethical leadership and the aforementioned features on other non-HR organizational actors. More specifically, this research examined how these individuals judge the acceptability of three ethically dubious HR management (HRM) practices: discrimination, disregard for the individual, and favor shown to those in power. Results obtained for data collected through an online survey indicate that ethical leadership is negatively associated with the acceptability of all three practices. Individuals in organizations with a strong ethical infrastructure also find discrimination and a disregard for the individual less acceptable. The same is true of participants in organizations perceived as more socially responsible regarding employees and economic aspects.